2010
DOI: 10.1002/mc.20666
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Akt/NF‐κB pathway in N6‐isopentenyladenosine‐induced apoptosis in human breast cancer cells

Abstract: N(6)-isopentenyladenosine (i6A) inhibits the tumor cell growth by inducing cell apoptosis in various cancer cell lines. However, little is known regarding the mechanisms by which the drug induces cell apoptosis. In this study, we further explored the molecular mechanisms of i6A as an anticancer agent on a human breast cancer cell line MDA MB 231. Treatment with i6A decreased the cell proliferation of MDA MB 231 cells in a dose-dependent manner by arresting the cells at G(0)/G(1) phase. This effect was strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…induction of apoptosis via c-JUN NH 2 -terminal protein kinase signaling, or blocking cell cycle by inhibition of NF-κB signaling), contrasting cancer progression. Similarly, i 6 A has been reported to inhibit cell cycle progression [11,14,15] and induce apoptosis through the inhibition of NF-κB signaling [14]. It is interesting to note that i 6 A and its analogs, in addition to their activation of the NRF2-mediated antioxidant response, also modulated genes in the p53 signaling pathway, although at lower statistical significance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…induction of apoptosis via c-JUN NH 2 -terminal protein kinase signaling, or blocking cell cycle by inhibition of NF-κB signaling), contrasting cancer progression. Similarly, i 6 A has been reported to inhibit cell cycle progression [11,14,15] and induce apoptosis through the inhibition of NF-κB signaling [14]. It is interesting to note that i 6 A and its analogs, in addition to their activation of the NRF2-mediated antioxidant response, also modulated genes in the p53 signaling pathway, although at lower statistical significance.…”
Section: Discussionmentioning
confidence: 95%
“…Based on biochemical research using cultured cells, different mechanisms of action for i 6 A have been suggested, including induction of apoptosis [14,17], inhibition of cell proliferation [15,18] or protein prenylation [12], and activation of the A3 adenosine receptor [19]. Using a different approach, gene expression analysis of i 6 A-treated MCF7 and A549 cells (from human breast adenocarcinoma and lung carcinoma, respectively), we found that the inhibitory effects of this compound were associated with the induction of several genes known to be activated during cell cycle arrest in response to stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, apoptotic mechanism of MCF-7 cell by cisplatin or l -PPMP is still unknown (Basu et al 2004b, c ;Boyle et al 2006 ;Yuan et al 2011 ;Leung et al 2011 ;Ullah et al 2011 ;Marchetti et al 2011 ;Kim et al 2010 ;Laezza et al 2010 ;Wesierska et al 2011 ;Chou et al 2010 ;Zhang et al 2010 ;Patil et al 2010 ) . Quercetin (a natural polyphenolic compound) induced apoptosis in many human cancer cells, including MCF-7 human breast cancer cells (Chou et al 2010 ) .…”
Section: Induction Of Apoptosis In Breast Cancer Cells By Novel Agentsmentioning
confidence: 96%
“…16.3 ) (Basu et al 2004a ) occurs in those cell lines at much higher concentrations (50-150 m M) (Boyle et al 2006 ) by EBRAP followed by activation of caspase-8 ( Fig. 16.3 ) Several new chemicals have been tested in recent years for induction of the apoptotic process by activating IMCAP (internal mitochondrial caspase activating pathway), NF-kappaB (NFKBAP), EBRAP (external Bad-receptor activating pathway), or CPKAP pathway (Yuan et al 2011 ;Leung et al 2011 ;Ullah et al 2011 ;Marchetti et al 2011 ;Kim et al 2010 ;Laezza et al 2010 ;Wesierska et al 2011 ;Chou et al 2010 ;Zhang et al 2010 ;Patil et al 2010 ;Banerjee et al 2010 ;Shirure et al 2011 ;Cazet et al 2010 ) . We also tested activation of apoptosis via all other pathways given in Table 16.1 in the above mentioned cell lines using those apoptotic agents ( Fig.…”
Section: Induction Of Apoptosis In Breast Cancer Cells By Novel Agentsmentioning
confidence: 97%
“…17 It is also known to suppress cell proliferation and inhibits DNA synthesis in lung cancer cells, 18 and that it reduces cell growth of human breast cancer through inhibition of AKT and prevention of translocation of NF-κB into the nucleus. 19 Reports have implicated that iPA could influence cytotoxic activity and cytokines production in natural killer (NK) cells and exert topical anti-inflammatory activity in mice. 20 Intriguingly, TRAF6 is upstream of JNK as well as AKT and NF-κB in IL-1R/TLR-mediated signaling pathways, its potential involvement in iPA-induced anti-cancer activities is not clear.…”
Section: Introductionmentioning
confidence: 99%